OPTIMALISASI FERMENTASI SUSU KAMBING ETAWAH DENGAN KURMA DAN MADU TERHADAP PENINGKATAN PROBIOTIK - Nanda Fatmala; Aidil Amar; Aiya Sofia (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2026)
Etawah goat milk has the potential to be developed as a functional food through a fermentation process with the addition of natural ingredients. This study aimed to evaluate the effect of different concentrations of dates and honey on the Total Plate Count (TPC) and acidity level (pH) of fermented Etawah goat milk. The study applied an experimental method using a 3×3 factorial Completely Randomized Design (CRD) with two replications. The goat milk was pasteurized, inoculated with Lactobacillus plantarum and Streptococcus thermophilus, and supplemented with dates and honey. The fermentation process was then carried out for 24 hours at 37°C. The results showed that the addition of dates and honey had a highly significant effect (P<0.01) on TPC values, but no significant effect (P>0.05) on pH values. The TPC values ranged from 32.5–221×10? CFU/mL with pH values of 4.5–5.0, and all treatments met probiotic standards.Key words: Etawah goat milk, fermentation, dates, honey, probiotics